Characterization and comparison of lesions on ornamental sweetpotato 'Blackie', tomato 'Maxifort', interspecific geranium 'Caliente Coral', and bat-faced cuphea 'Tiny Mice'. - Craver, Joshua K.; Miller, Chad T.; Williams, Kimberly A.; Boyle, Daniel L. (My University, 2014)
Many plant species are prone to physiological disorders in which lesions develop on the leaf tissue. Nomenclature for such lesions has included intumescences, excrescences, neoplasms, galls, genetic tumors, enations, and oedemata. Interchangeably using these terms causes confusion as to whether these names refer to the same or different disorders. Two of the most commonly used names are oedema and intumescence. The objective of this research was to characterize the development of lesions on ornamental sweetpotato (Ipomoea batatas ‘Blackie’), tomato (Solanum lycopersicum ‘Maxifort’), interspecific hybrid geranium(Pelargonium· ‘CalienteCoral’), and bat-faced cuphea (Cuphea llavea ‘TinyMice’) to determine similarities and differences in morphology and nomenclature among these physiological disorders. Light microscopy was used to characterize differences in cross-sectional height, width, and area of lesions on each species. Additionally, leaf tissue samples were embedded in paraffin, and 10-mm cross-sections were stained with Toluidine blue O and observed using light microscopy to identify specific cell layers involved with lesion development. Field emission scanning electron microscopy (SEM) and digital photography were used to observe the microscopic and macroscopic stages of lesion development, respectively, on each species. The lesions observed on ornamental sweetpotato were significantly greater in height and area than on the other three species, whereas tomato lesions were significantly greater in width. Lesions on ornamental sweetpotato and bat-faced cuphea occurred predominantly on the adaxial surface of the leaf, whereas lesions on geraniumand tomato occurred predominantly on the abaxial surface.With lesions on tomato, ornamental sweetpotato, and bat-faced cuphea, the epidermis was often subjected to the same hypertrophy apparent in the underlying parenchyma cells, ultimately allowing for greater cell expansion. However, in geranium, the epidermis resisted the expansion of the underlying cells, resulting in the eventual tearing of this tissue layer. Previous research indicates that lesion development on geranium is closely related to water status within the plant and may result in a wound response or provide a means of facilitated gas exchange. On the contrary, development of lesions on ornamental sweetpotato and tomato is believed to involve light quality. Based on these results and observations, two disorders occur across these species. The term "intumescence’’ should be used when referring to abnormal lesions on ornamental sweetpotato and tomato, and the term ‘‘oedema’’ should be used when referring to lesions on geranium. The term ‘‘intumescence’’ should also be used when referring to bat-faced cuphea lesions resulting from the morphological and anatomical aspects of these lesions closely resembling development on ornamental sweetpotato and tomato. Future research should investigate the role of light quality regarding development on this species.
Keywords: Cuphea llavea; Ipomoea batatas; Oedema; Intumescence; Pelargonium; Solanum lycopersicum